Revitalisasi Studi Hisab di Indonesia - Susiknan Azhari (Al-Jami'ah: Journal of Islamic Studies, 2000)
This article tries to look at the study of Science of Islamic Calendar (Ḥisab) in Indonesia. In the first part of this writing, the writer shows the golden age of this science when such great Islamic scientists as al-Khawārizmi, al-Battany, al-Birūni and Ulugh Beg, flourished. The writer argues that this development was achieved because there was no dichotomy between this Science of Islamic Calendar and Astronomy. However, currently, study of Science of Islamic Calendar in the Muslim world, particularly in Indonesia, has stagnated. By examining bibliography on this study, the writer surveys the causes of this stagnancy. According to him, this condition is caused by frame of thought of dichotomy between religious knowledge and science, which in tum leads to the dichotomy between the Science of Islamic Calendar and Astronomy. The former is identified as one of religious matters and the latter is regarded as a "pure science" which has its own authority. Religion, then, regards as something that is difficult to attain and does not touch the reality; while the science develops in accordance with the needs of times. As a result, Astronomy develops rapidly; while the Science of Islamic Calendar stagnates. To deal with this problem, the writer suggests that in order to revitalize the Science of Islamic Calendar in Indonesia, Muslims must return the science to its origin as part of religious function and stop the dichotomy between the Science of Islamic Calendar and Astronomy by regarding the needs of time.